Participation and decision making: a three-person power-to-take experiment - Max Albert; Vanessa Mertins (Philipps-University Marburg, Faculty of Business Administration and Economics, 2008)
It is often conjectured that participatory decision making may increase acceptance even of unfavorable decisions. The present paper tests this conjecture in a three-person power-to-take game. Two takers decide which fraction of the responder's endowment to transfer to themselves; the responder decides which part of the endowment to destroy. Thus, the responder can punish greedy takers, but only at a cost to herself. We modify the game by letting the responder participate in takers' transfer decision and consider the effect of participation on the destruction rate. We find that participation matters. Responders destroy more if they (1) had no opportunity to participate in the decision making process and (2) are confronted with highly unfavorable outcomes. This participation effect is highly significant for those responders (the majority) who show negative reciprocity (i.e., destroy more when takers are greedier).
Keywords: C72; C91; D72; 330; fairness; participatory decision making; power-to-take game; procedural fairness